A Metronome Guide to High Quality Cardiac Pulmonary Resuscitation in Nursing Laboratory Learning - Darwati, Lestari Eko; Prasasti, Selly; Setianingsih, Setianingsih; Asyrofi, Ahmad (Babali Publisher, 2023)
Introduction: Cardiac arrest is the first cause of death in the world. The quality of compression during CPR given to someone experiencing cardiac arrest greatly influences their survival. Nursing students have an important role in rescue efforts. The low quality of compression during CPR simulations in the nursing laboratory for nursing students is the basis for the need for innovation to improve it. A metronome is a tool that can be used because it can produce rhythmic and clear beats with a programmed frequency. The aim of this study was to determine the effect of using a metronome on chest compression speed during CPR. Methods:The study used quasi Experiment pretest post-test without control groups. The sample was female students from the Nursing Study Program. The sampling technique uses purposive sampling. Results:The research results showed that the pre-intervention average was 126 x/minute and the post-intervention average was 117 x/minute. The Wilcoxon test results obtained a p value of 0.036 (p <0.05), which means that there is an influence of metronome use on chest compression speed. Conclusion: A metronome can be used as a guide to achieve standardized chest compression speeds in nursing laboratory learning. Key words: CPR, chest compression, metronome speed